Electronic medical record and its impact on health care and management. A systematic review between the years 2013 – 2023 - Morales-Camargo, José; Meneses-Claudio, Brian (Salud, Ciencia y Tecnología - Serie de Conferencias, 2023)
The adoption of Electronic Health Records (EHR) has revolutionized the landscape of healthcare and healthcare management in recent decades. These technological systems have been the subject of extensive interest and study to understand their impact on improving patient care and efficiency in health management. For this reason, this study proposes to evaluate the impact of the use of electronic medical records on health care and management. In addition, the study includes a systematic review of the literature of research carried out between 2013 and 2023 on the use of the Electronic Health Record (EHR) focused on patient care and health management. The PICO methodology was used to formulate the search equation in the Scopus database. To select the studies, the PRISMA methodology was used through 3 stages: identification, screening, and inclusion, obtaining a total of 17 articles for review, according to inclusion and exclusion eligibility criteria. At the beginning of the systematic search, 56400 studies were found, 5220 were related to health care, 244 researchers work carried out between 2013 and 2023 focused on health management. Also, 17 studies obtained at the end of the third search stage, 42,11 % indicated that the EHR facilitates medical care, 21,05 % indicated that it provides better safety and greater patient satisfaction. On the other hand, 36,36 % and 45,45 % mentioned that with the EHR there is a good quality of care and better clinical management, respectively, compared to the use of paper medical records. In conclusion, the EHR offers benefits in medical care and facilitates decision making at the health management level. Its interoperability means that clinical management is integrated with all other medical systems to provide quality care, despite certain limitations that persist in the health field.